2017
DOI: 10.5539/ies.v10n7p143
|View full text |Cite
|
Sign up to set email alerts
|

Development of Program to Enhance Team Building Leadership Skills of Primary School Administrators

Abstract: Team building leadership skills are important to understandings of how the primary school administrators might work towards creating more effective teamwork in the school. This research aimed 1) to study the components of team building leadership skills needed for primary school administrators, 2) to examine the current states and desirable conditions and needs for team building leadership skills of primary school administrators, 3) to develop team building leadership skills for primary school administrator en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…4. Teamwork: The teamwork skill is one of the skills necessary to accomplish most of the work, given the need of individuals and the necessity of cooperation and teamwork tasks, for the ability to achieve and benefit from the strengths of team members to reach goals and save time and effort explained (Sairam et al, 2017). The work team consists of several individuals with multiple and different skills and integrated work dynamics to reach joint teamwork and achieve goals, and the skill of work teams is one of the leadership skills that urge the leader to exert influence on other members of the organization, and help that organization achieve goals effectively and efficiently.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…4. Teamwork: The teamwork skill is one of the skills necessary to accomplish most of the work, given the need of individuals and the necessity of cooperation and teamwork tasks, for the ability to achieve and benefit from the strengths of team members to reach goals and save time and effort explained (Sairam et al, 2017). The work team consists of several individuals with multiple and different skills and integrated work dynamics to reach joint teamwork and achieve goals, and the skill of work teams is one of the leadership skills that urge the leader to exert influence on other members of the organization, and help that organization achieve goals effectively and efficiently.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Teaching inter professional teamwork skills to health professional students was in focus of L. Fox, R. Onders, C. J. Hermansen-Kobulnicky, T. Nguyen, L. Myran, B. Linn and J. Hornecker [7]. B. Sairam, C. Sirisuthi and K. Wisetrinthong [27] in their findings showed that teambuilding leadership skills enhancement program have five toolkits, applying which the primary school administrators could manage their teamwork more efficiently and the overall progress of team building could become more successful.…”
Section: Literature Reviewmentioning
confidence: 99%